Can the riparian invader, Arundo donax, benefit from clonal integration?. (13th July 2013) - Kui, L; Li, F; Moore, G; West, J
Summary: Resource sharing through rhizomes of clonal plants supplements locally available nutrients to enhance recruitment and growth in resource‐limited environments. We investigated whether Arundo donax, an invasive clonal plant, can benefit from clonal integration. Sharing resources between ramets can facilitate resprouting from mowing, fire and herbicide treatments, but it is unknown whether clonal integration contributes to A. donax invasion success. Our first objective was to determine whether A. donax rhizomes transported water between ramets. Hydrogen isotopic–enriched water was applied on three 1 m diameter areas, and rhizome and soil samples were collected beyond the watering zone after 5, 24 and 48 h of the last watering. Logistic modelling indicated that water was able to move laterally at least 3.5 m. The second objective was to determine whether clonal integration enhanced growth and survival of A. donax ramets. We compared growth‐related responses in paired 1 m 2 plots with severed and intact rhizomes. In the first 19 days, rhizome severing nearly doubled ramet density, while by 77 days, the intact rhizomes produced 67% taller stems with 49% greater diameter and showed higher survival rate after flooding. This study provides initial evidence that physiological integration could be an important mechanism in A. donax, which can enhance its competitive abilities, accelerate rates of encroachment and strengthen its capability to recolonise disturbed areas. Our results highlight an important consideration of clonal invasive species in weed management.